2019
DOI: 10.1002/ajhb.23218
|View full text |Cite
|
Sign up to set email alerts
|

Birth mode, breastfeeding and childhood infectious morbidity in the Yucatec Maya

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
0
10
0
1
Order By: Relevance
“…The rural Yucatec Maya study community is located in the Puuc region of Yucatan about 140 km southwest of Merida. The community consists of ~500 subsistence maize agriculturalists whose economy, demography and childcare practices have been studied extensively since 1992 (Kramer, 2005; Kramer, 2009; Kramer & Veile, 2018; Veile, Faria, et al, 2019; Veile & Kramer, 2018). The past 20 years have seen the introduction of electricity, running water, a paved road, motorized vehicles, mechanized farming, schools, and a health clinic, yet villagers maintain a largely traditional diet and agricultural practices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rural Yucatec Maya study community is located in the Puuc region of Yucatan about 140 km southwest of Merida. The community consists of ~500 subsistence maize agriculturalists whose economy, demography and childcare practices have been studied extensively since 1992 (Kramer, 2005; Kramer, 2009; Kramer & Veile, 2018; Veile, Faria, et al, 2019; Veile & Kramer, 2018). The past 20 years have seen the introduction of electricity, running water, a paved road, motorized vehicles, mechanized farming, schools, and a health clinic, yet villagers maintain a largely traditional diet and agricultural practices.…”
Section: Methodsmentioning
confidence: 99%
“…Mothers engage in domestic tasks (e.g., cooking, laundry, and childcare) and some field work; some earn cash by participating in government‐run craft cooperatives (Hackman & Kramer, 2021). The rural Maya are bilingual in Spanish and Maya, with Maya being the predominate language spoken within households and children's first language (Padilla‐Iglesias & Kramer, 2021) Previous studies showed a median breastfeeding duration of 30.64 months (95% CI: 29.62–31.66, n = 88), with the introduction of complementary foods occurring at a median of 5.7 ( SD =2.2, range =2–12, n = 58) months (Veile, Faria, et al, 2019; Veile & Kramer, 2015). Mothers completed on average 6.52 ( SD =3.10, n = 73) years of schooling (Kramer et al, 2021; Veile, Valeggia, & Kramer, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with these guidelines, mothers do not practice it because of a range of reasons [ 3 ]. Thereby creating a cave of early infant diagnosis (EID) of morbidities to infants as it is influenced by the feeding choice that the mothers make [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is essential to understanding species‐wide variation in reproductive functioning. Many overt features of human reproduction (eg, the number and timing of births (Beall & Leslie, 2014), breastfeeding behaviors (Veile, Faria, Rivera, Tuller, & Kramer, 2019), and menstrual bleeding (Fitzpatrick, 2018)) can be studied without recourse to measuring hormones. Nonetheless, the addition of these and other biomarkers opens a window into reproductive mechanisms not otherwise accessible.…”
Section: Introductionmentioning
confidence: 99%